PENENTUAN WAKTU BAKU DALAM PENGECEKAN BONDING SAMPEL SEPATU PADA PT. CHING LUH INDONESIA - Sutaarga, Ossa; Setiawan, Alfiandy (Journal Industrial Manufacturing, 2021)
PT. Ching Luh Indonesia is a company engaged in the manufacturing industry that produces sports shoes with well-known global brands, with annual revenues of more than US $ 1 billion, and has 8,000 workers. PT. Ching Luh Indonesia is a company that is responsive to technological advances and pays great attention to the comfort of employees in working, especially in the Laboratory section. In that section, the bonding checking process on the shoe samples currently still uses direct checking without any time reference in each sample. This is considered less effective because it makes the addition of the remaining sample for the next shift. This study aims to determine the standard time of each shoe sample variant and to determine the number of samples received by each operator. From the research results using the calculation of the standard time can be determined the standard time of each variant of the shoe sample, so it can also be determined the number of samples received for each operator. By determining the standard time for each shoe sample, it is expected that each operator can complete each sample according to the predetermined standard time, so that the specified target can be achieved.. Keywords: Standard Time, Bonding, Shoe Samples, Laboratory, Operator